Oxide Thermoelectric Materials : from Basic Principles to Applications - Lin, Yuan-Hua (Wiley-VCH, 2019)
The first book of its kind?providing comprehensive information on oxide thermoelectrics This timely book explores the latest research results on the physics and materials science of oxide thermoelectrics at all scales. It covers the theory, design and properties of thermoelectric materials as well as fabrication technologies for devices and their applications. Written by three distinguished materials scientists, Oxide Thermoelectric Materials reviews: the fundamentals of electron and phonon transport; modeling of thermoelectric modules and their optimization; synthetic processes, structures, and properties of thermoelectric materials such as Bi2Te3- and skutterudite-based materials and Si-Ge alloys. In addition, the book provides a detailed description of the construction of thermoelectric devices and their applications.-Contains fundamentals and applications of thermoelectric materials and devices, and discusses their near-future perspectives -Introduces new, promising materials and technologies, such as nanostructured materials, perovskites, and composites -Paves the way for increased conversion efficiencies of oxides -Authored by well-known experts in the field of thermoelectrics Oxide Thermoelectric Materials is a well-organized guidebook for graduate students involved in physics, chemistry, or materials science. It is also helpful for researchers who are getting involved in thermoelectric research and development.
Keywords: Thermoelectric materials.; Thermoelectric apparatus and appliances.; elektronické knihy; electronic books